Kerugian Infrastruktur Kawasan Permukiman Rentan Banjir di Sub DAS Bendung Kota Palembang - Legislatifa, Poppy Augustina; Nisumanti, Sartika (Jurnal Talenta Sipil, 2025)
Palembang City's routine problems in dealing with flooding are quite extensive and long, one of which occurs in the Bendung Watershed (DAS). Flooding in the Bendung watershed area is influenced by several things, including natural factors such as the characteristics of the river which has a small river flow capacity, the ebb and flow of sea water in the river and the relatively flat topographic conditions so that some areas of the Bendung watershed are floodplains. The purpose of this study is to measure the height or inundation of floods and the length of time of flood inundation in flood-prone areas in residential areas along the Bendung watershed area, identify risk elements and assess the risks experienced by residents around the Bendung River due to the influence of flooding or flood inundation with the condition of the residents' vulnerability. The method used in this research is direct observation (questionnaire) about infrastructure losses in vulnerable residential areas (easily affected by flooding) in Palembang City. The results of this study obtained an average flood event of 37.5 times. The risk value experienced by residents in the Bendung watershed area occurs every year, with a probability value of 0.930. For the largest risk value in the land elevation area 0-5 m or on the banks of the Bendung River is 63.24 with a depth of 50 cm and the number of submerged houses reaches almost 68 houses. In the 5-10 m land elevation area is 79.98 with a depth of 20 cm and the number of submerged houses is almost 86 houses.